2022
DOI: 10.1007/s12325-022-02132-2
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Treatment Response to Ixekizumab Categorised by Sex in Radiographic and Non-radiographic Axial Spondylarthritis Through 52 Weeks: Data from Three Phase III Randomised Controlled Trials

Abstract: Objectives Assess baseline characteristics and treatment response to ixekizumab (IXE) categorised by sex in patients with radiographic axial spondyloarthritis (r-axSpA) and non-radiographic axSpA (nr-axSpA) up to 52 weeks. Methods Data were analysed from three randomised controlled trials of IXE through 52 weeks. Patients fulfilled ASAS classification criteria for r-axSpA or nr-axSpA and were randomised to receive 80 mg subcutaneous administration of IXE every 2 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, male and female patients with axSpA tend to differ in their responses to treatment. In this Review, we discuss sex and gender differences and how they might con tribute to differences in phenotypes and therapeutic responses in axSpA [13][14][15][16][17][18][19] .…”
Section: Sexual Dimorphism In the Prevalence Manifestation And Outcom...mentioning
confidence: 99%
“…Interestingly, male and female patients with axSpA tend to differ in their responses to treatment. In this Review, we discuss sex and gender differences and how they might con tribute to differences in phenotypes and therapeutic responses in axSpA [13][14][15][16][17][18][19] .…”
Section: Sexual Dimorphism In the Prevalence Manifestation And Outcom...mentioning
confidence: 99%
“…Long considered mainly a disease of men, particularly ankylosing spondylitis, has more recently been reported to also affect a subset of females ( Masi, 1992 ; Wright et al, 2020 ; Cunha et al, 2022 ; Marzo-Ortega et al, 2022 ; Stovall et al, 2022 ). Sex differences in disease presentation characteristics ( Chimenti et al, 2021 ), as well as disease activity compared to males have been reported, with females exhibiting higher disease activity than males and exhibiting different response patterns to clinical interventions ( Mease et al, 2021 ; Stovall et al, 2022 ; van der Horst-Bruinsma et al, 2022 ).…”
Section: Influence Of Sex On Msk Tissues As An Adultmentioning
confidence: 99%
“…Taking into account how the gender differences might have an impact on SpA outcomes, van der Horst-Bruinsma and colleagues observed that male patients had a better and more rapid response to IXE than women, who experienced worse outcomes, especially those with a diagnosis of nr-axSpA (75).…”
Section: Enthesitis Is a Hallmark Of As Beingmentioning
confidence: 99%
“…• In axSpA patients treated with ixekizumab, a withdrawal of the drug, the presence of anti-drug antibodies, an abnormal BMI and higher values of C-reactive protein or ASDAS were shown to be risk factors for disease flares. Moreover, female sex and a diagnosis of nr-axSpA seem to be associated with reduced efficacy of the drug (74,75). • Brodalumab was effective and safe in Asian patients with both r-and nr-axSpA (76).…”
Section: Jak-inhibitorsmentioning
confidence: 99%